Pokémon. Sword & shield. Volume 7 - Kusaka, Hidenori (Pokémon., 2023)
Casey Shield, a hacker who invented the Dynamax Simulator, and Henry Sword, a boy who repairs gear for Pokémon, both dream of entering the Galar region's Gym battles. For Casey, it's a chance to reunited with her lost Pokémon. For Henry, it's an opportunity to search for the legendary Rusted Sword and Rusted Shield. Henry adds the Comedian Pokémon Mr. Rime to his team and names it Kayne. After a complicated but ultimately successful Gym battle, Henry and Casey head to Spikemuth, where they are confronted by two Pokémon who are obviously being controlled by someone.